Effects of Metal-Ion Substitution on the Structural, Morphological, and Electrochemical Properties of Lifexznymn2−X-Yo4 (X, y = 0.25 or 0.75) - Vargas-Norambuena, J; Escrig-Murua, J; Alburquenque-Munoz, D; Alburquenque-Munoz, D; Tasca-Gottardo, F; Tasca-Gottardo, F; Zúñiga-Loyola, C; Zúñiga-Loyola, C (Elsevier Ltd, 2024)
The oxides LiMn2O4, LiFe0.75Zn0.25MnO4, and LiFe0.25Zn0.25Mn1.5O4, referred to as LMO, LFZMO 0.75–0.25, and LFZMO 0.25–0.25, were synthesized at 800 °C using ultrasound-assisted thermal decomposition of nitrates (UA-TDN). X-ray diffraction (XRD) analyses confirmed the spinel structure (Fd3m space group) for all materials. Raman spectroscopy validated the characteristic absorption bands of the spinel phase. Energy-dispersive spectroscopy (EDS) verified the uniform distribution of Fe, Zn, Mn, and O in all samples and proved the expected stoichiometry for the different oxides. Scanning electron microscopy (SEM) images showed irregular polyhedral agglomerates in the synthesized oxides, with grain sizes ranging from approximately 600 to 800 nm. Electrochemical characterization was performed under N2 and O2 atmospheres, revealing electron-withdrawing effects with increasing iron content in the oxide composition. LFZMO 0.75–0.25, with a higher iron content, displayed better performance than LMO and LFZMO 0.25–0.25 in terms of discharge capacity and cycling performance at various rates. The greater discharge capacity of LFZMO 0.75–0.25 (47 mA h g −1) was in line with the cyclic voltammetry findings, wherein lower energy (∆GLi+/ Li0 = 55.5 kJ mol−1) for lithium insertion correlated with an increased discharge capacity. Electrochemical Impedance Spectroscopy (EIS) was employed to determine diffusion constants, providing insights into Li+ insertion kinetics in the cathodic electrode and highlighting the significant influence of Zn and Fe incorporation on the lithium manganese oxide. Our findings are intriguing as the diffusion coefficient of DLi+ in LFZMO 0.75–0.25 (2.3 ×10−12 cm2 S−1) surpasses that of LMO (8.5 ×10−14 cm2 S−1) and LFZMO 0.25–0.25 (9.4 ×10−18 cm2 S−1). This observation further elucidates the more positive formal potential for Li+ insertion in LFZMO 0.75–0.25. © 2023 Elsevier B.V.